Studi Evaluasi Pengelolaan Kelas pada Pembelajaran Outdoor di Kelas VA SDN 08 Kota Bengkulu - Permata, Syahnora Dwi; Alexon; Lusa, Herman (JURIDIKDAS, 2024)
This study aims to evaluate classroom management in outdoor learning at SD Negeri 08 Bengkulu City. This research is an evaluation research using the discrepancy evaluation model. The subjects of this research were VA class teachers and VA class students. Qualitative data were obtained from observation sheets, interviews and documentation. This study uses a qualitative selection of considerations and uses the Miles and Huberman model of analysis techniques. The results show that the arrangement of students and facilities in the implementation of classroom management in learning outside the classroom (outdoor learning) has been successful because it has implemented the set standard. The number of occurrences of each indicator is mostly (5) very good, (4) good, and (3) sufficient. Therefore the implementation of classroom management in learning outside the classroom can be said to have been successful. The implementation of learning outside the classroom (Outdoor Learning) is in accordance with the provisions that are enforced even though there are several descriptors that do not appear.